Implementasi Nilai-Nilai Pancasila dalam Pembangunan Hukum Tata Negara di Indonesia - Fatroyah Ars Himsyah; Muhammad Abdillah; Abdul Malik (Pusat Pengkajian Pancasila dan Konstitusi (PUSKAPSI) FH UNEJ, 2025)
This paper explores the pivotal role of Pancasila as the foundational philosophy and normative source in the development of Indonesia’s national legal system. The study addresses the challenge of aligning legal reconstruction with the cultural identity of the Indonesian nation, while simultaneously adapting to societal dynamics and advances in science and technology. Employing a qualitative normative research methodology, the paper analyzes legal doctrines, constitutional provisions, and philosophical underpinnings related to Pancasila's integration into lawmaking processes. The findings underscore that Pancasila serves as an indispensable framework that ensures the national legal system reflects the core values of justice, democracy, human rights, and social welfare inherent to Indonesian society. Furthermore, the research highlights the necessity of grounding legal reform on these values to foster a just and sustainable legal order. The study contributes to the ongoing discourse on legal development by emphasizing the harmonization of indigenous values with contemporary legal demands. Recommendations for future research include empirical investigations into the practical implementation of Pancasila-based legal principles across diverse regional contexts.